Design of a real time quantitative PCR assay to assess global mRNA amplification of small size specimens for microarray hybridisation. Issue 12 (24th November 2004) - Choesmel, V; Foucault, F; Thiery, J P; Blin, N
Abstract : Background: Low RNA yields from clinical samples are a limiting step for microarray technology. Aims: To design an accurate real time quantitative polymerase chain reaction (PCR) assay to assess the crucial step of global mRNA amplification performed before microarray hybridisation, using less than 1 µg total RNA. Methods: Three RNA extraction procedures were compared for small size samples. Total RNA was amplified from universal RNA or the BC-H1 breast cancer micrometastatic cell line using three different protocols. Real time quantitative PCR technology was used for accurate measurement of urokinase plasminogen activator receptor and cytokeratin 8 RNA amplification rates and ratios, using primer sets binding at various distances from the 3′ end of transcripts. A 50 mer oligomeric array targeting 87 genes potentially involved in breast cancer metastatic progression was built and hybridised with amplified RNA. Results: Eighteen nanograms of total RNA could be purified from 1000 BC-H1 micrometastatic cells. Amplification rates of 25 000 to 100 000 were achieved with as little as 10 ng of starting material. However, results were highly variable, depending on the amount of starting material, gene characteristics, sample quality, and protocols used. Oligomeric array hybridisation with 20 µg reference RNA resulted in specific and reproducible signals for 83% of the genes, whereas mRNA amplification from less than 400 ng of starting material resulted in selective detection of signals from highly expressed genes. Conclusions: Improvements in the design of global mRNA amplification procedures and oligomeric arrays are needed to extract informative gene expression data from clinical samples containing limited cell numbers.